DISTRIBUTION OF HERITAGE AND CULTURE IDDAH MINANG DIVORCE IN WHICH IMPLEMENTED IN THE LAW NUMBER 1 YEAR 1974 ON MARRIAGE - Putri Maha Dewi (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
Divorce is the dissolution, which has been fostered by married couples caused by several things such as death and the decision of justice. In this case the divorce is seen as the end of an instability of marriage where married couples live apart and Seara then officially recognized by applicable law. In Act No. 1 1974, namely Article 11 (1) For a valid marriage that broke up the waiting period. (2) The period of time the waiting period of paragraph (1) shall be regulated further in a government regulation. In indigenous cultures also known'Iddah Minang, the waiting period for a woman whose divorce from her husband to be able to mate again, in order to know whether women are pregnant or not. If the woman was pregnant, then he is allowed to marry again after her son was born, when she was not pregnant, then she had to wait 4 months 10 days and if divorced because the husband dies or 3 times the holy of menstruation if life due to divorce. While traditional Minang cultural heritage division contrary to the division of inheritance according to Law No. 1 Year 1974 about marriage. In a culture known as the Minang traditional matrilineal system thus indirectly all the treasures bequeathed to the daughter. In Act No. 1 of 1974 on Marriage, inheritance is the joint property